2023
DOI: 10.14293/s2199-1006.1.sor-.pple5eh.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dementia in India: An Overview

Abstract: Dementia is a rapidly growing concern in India, with a projected increase in the number of affected individuals in the coming years. People over the age of 60 are expected to account for 19.1% of the overall population by 2050. This population ageing is likely to be accompanied by a significant increase in the prevalence of dementia. A number of prospective longitudinal investigations on the aetiology of dementia have been conducted in North America and Europe; however, the conclusions of this research cannot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…The diversity and abundance of weed species in pulse crops are influenced by soil characteristics, farming practices, and climatic conditions [14]. Different pulses have specific critical periods when they are vulnerable to weed interference (Tables 1 and 2) [15]. Chickpea (Cicer arietinum L.) ranks as the world's third most vital pulse crop enriched in protein and other vital nutrients.…”
Section: Weed Interference In Pulse Cropmentioning
confidence: 99%
See 2 more Smart Citations
“…The diversity and abundance of weed species in pulse crops are influenced by soil characteristics, farming practices, and climatic conditions [14]. Different pulses have specific critical periods when they are vulnerable to weed interference (Tables 1 and 2) [15]. Chickpea (Cicer arietinum L.) ranks as the world's third most vital pulse crop enriched in protein and other vital nutrients.…”
Section: Weed Interference In Pulse Cropmentioning
confidence: 99%
“…Over the past few decades, numerous genes have been identified that confer herbicide tolerance in valuable crops. This tolerance can result from mutations in native genes or the introduction of foreign Top 10 herbicides and the corresponding number of resistant species they are linked to [15].…”
Section: Development Of Herbicide-resistant Crop Via Mutagenesismentioning
confidence: 99%
See 1 more Smart Citation